2011
DOI: 10.1037/a0022896
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of a disclosure intervention for HIV+ mothers: The TRACK program.

Abstract: Objective-The Teaching, Raising, And Communicating with Kids (TRACK) program was a longitudinal pilot-trial intervention designed to assist mothers living with HIV (MLH) to disclose their serostatus to their young children (age 6 -12 years).Method-MLH and child dyads (N = 80 dyads) were recruited and randomized to intervention or control; the intervention group had three individual sessions and one follow-up phone call. The sessions focused on preparing MLH for disclosure through behavioral exercises utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 46 publications
3
118
0
Order By: Relevance
“…The Teaching, Raising, And Communicating with Kids (TRACK) programme was developed and evaluated in a small pilot randomized control trial [13]. Mothers in the intervention group were six times more likely to disclose than mothers in the control arm, with roughly one-third of the mothers in the intervention arm disclosing, while only 7.8% of mothers in the control arm disclosed their serostatus.…”
Section: Introductionmentioning
confidence: 99%
“…The Teaching, Raising, And Communicating with Kids (TRACK) programme was developed and evaluated in a small pilot randomized control trial [13]. Mothers in the intervention group were six times more likely to disclose than mothers in the control arm, with roughly one-third of the mothers in the intervention arm disclosing, while only 7.8% of mothers in the control arm disclosed their serostatus.…”
Section: Introductionmentioning
confidence: 99%
“…This research identified the following scientific evidence of factors that influence the decision to disclose parents' HIV diagnosis to children: cognitive ability and maturity of the child; strengthening of family ties; informing children about the disease; parents' illness or death; the possibility of discovery by third parties; stigma and prejudice; negative reactions by children; the way of speaking about the disease to the child; and fear of losing parental power [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 1, appendix).…”
Section: Resultsmentioning
confidence: 99%
“…The most common adverse reactions of children after the disclosure of paternal diagnosis was fear regarding their parents' state of health and life, and fear of being stigmatized by friends 30 . After disclosure, children can become frightened and shocked 31 .…”
mentioning
confidence: 99%
“…91,92 Given the important role of stigma in mediating the relationship between HIV and anxiety, interventions supporting disclosure may also be needed for the target population but remains a major challenge for parents and other caregivers in South Africa 93,94 and elsewhere. 95 Disclosure interventions have been tested in South Africa 96 and elsewhere 97 that could be tested for use among caregivers. Caregivers affected with both conditions are most vulnerable; it follows that development of psychological interventions to support these caregivers may need to incorporate a family-level approach.…”
Section: Discussionmentioning
confidence: 99%